Bacteria Foraging Algorithm Based Optimal Multi Sink Placement in Wireless Sensor Networks - Bose Pitchaimanickam; Gurusamy Murugaboopathi (Journal of Intelligent Systems, 2018)
Wireless Sensor Networks (WSN) are mainly utilized for time sensitive applications such as forest fire detection systems and health monitoring systems. Sensor nodes are operated on low power and limited computation process. It is essential to develop the solution for planning the topological area. Multiple sinks are located in the network and reduce the number of hops between the sensors and its sinks. We propose an efficient technique based on Bacteria Foraging Algorithm to identify the best optimal locations of sinks. The experimental results show that average end to end delay is minimized and average energy consumption of sensor nodes are reduced.